Jobs for North Lebanon : Value Chains, Labor Markets, Skills and Investment Climate in Tripoli and the North of Lebanon - World Bank Group (World Bank, Washington, DC, 2017)
This report provides an assessment of constraints and opportunities for the creation of more and better quality jobs for Lebanese in the more fragile and conflict-affected regions. The geographical focus is North Lebanon, including Tripoli. This analysis, accompanied by further dialogue with the key public and private sector professionals, can serve to inform the design and development of a jobs-focused program of financial support for North Lebanon. This diagnostic and program development approach can also be replicated in other high-priority, lagging regions of the country. The diagnostic followed a three-pronged approach in order to assess the gaps that need to be overcome to respond effectively to job opportunities, foster productivity, and increase earnings: 1) an assessment of the investment climate in North Lebanon; 2) a value chain analysis (VCA) of selected sectors and the interventions required to unlock competitiveness and job creation; and 3) a review of the supply of labor and skills in the region, a stock-taking of training providers. Enterprise surveys were conducted of the key agents in two targeted value chains, as well as a household-level skills survey of the working age population in North Lebanon. Complementary semi-structured interviews and focus group meetings were also undertaken. Consultations with the Government and other stakeholders took place from May through August, 2016.